Photocatalytic reduction of Uranium(VI) under visible light with Sn-doped In2S3 microspheres. (December 2018) - Feng, Jinna; Yang, Zhiquan; He, Shan; Niu, Xiaojun; Zhang, Taiping; Ding, An; Liang, Heng; Feng, Xiaochi
Abstract: Visible light-driven conversion of soluble U(VI) to slightly soluble U(IV) has been regarded as a efficient and environmentally friendly technology to deal with uranium containing wastewater. In this paper, we attempted to use photocatalytic technology to reduction U(VI) from aqueous solution by constructing a highly efficient photocatalysts. The novel Sn-doped In2 S3 microspheres photocatalyst were synthesized for the first time by a simple hydrothermal method, and characterized with various analytical and spectroscopic techniques to determine their structural, morphological, compositional, optical and photocatalytic properties. In determination of photocatalytic activity, the results showed that all Sn-doped In2 S3 samples exhibited greater photocatalytic performance in reduction of U(VI) under visible light than the pure In2 S3 . The optimum SnIn2 S3 photocatalyst with Sn:In molar ratio of 1:4.8 (SnIn2 S3 ) had the highest photocatalytic performance (95% reduction efficiency within 40 min irradiation time), which was approximately 15.60 times faster than that of pure In2 S3 . The enhanced photocatalytic activity of the optimum SnIn2 S3 was largely ascribed to the higher specific surface area, red-shift in the absorption band, the efficient separation of photogenerated electron-hole pairs (e − /h + ) and the narrowed band gap with an up shifting of valence band, conduction band potentials. In addition the optimum SnIn2 S3 photocatalyst exhibited a good recyclability and stability during the repetitive experiments. Finally, the possible active species and the possible mechanism on basis of the experimental results were discussed in detail. Graphical abstract: Highlights: Sn-doped In2 S3 microspheres were synthesized by a simple hydrothermal method. SnIn2 S3 showed high photocatalytic activity in reduction of U(VI) under vis-light. Sn doping expanded the light absorption region and improved charge separation. Band gap of SnIn2 S3 (2.09 eV) was narrower than that of un-doped In2 S3 .